Biomechanical Energy Harvesting: Effects of Orientations on Efficiency of Energy Harvesting from Heart Motion Using Ultrathin Flexible Piezoelectric Devices (Adv. Theory Simul. 7/2019). Issue 7 (1st July 2019) - Zhang, Yangyang; Lü, Chaofeng; Lu, Bingwei; Feng, Xue; Wang, Ji
Abstract : Harvesting biomechanical energy from heart motions using piezoelectric materials to power implantable devices has attracted increasing attention. In article number 1900050, Chaofeng Lü, and co‐workers develop an electromechanical model for flexible piezoelectric energy harvesters with the effects of myocardial fiber. The results may provide guidelines for optimizing patching orientation of flexible piezoelectric energy harvesters mounted on fibrous structures.